State Support of Mortgage Lending as a Condition for Ensuring Stable Development of the National Economy (Economics and region, 2021)
The issues of state support of mortgage lending in Ukraine as a tool to stimulate the housing market, expand the opportunities of a wide range of citizens to meet housing needs and ensure the stable development of the national economy are considered. The fragmentation of the state housing policy and various instruments of state support for housing market participants are noted. Emphasis is placed on the significant unrealized potential of the construction sector, whose contribution to the domestic economy is three times smaller than the European average. The state and dynamics of the housing stock of Ukraine, the development of which remains highly sensitive to changes in the economy, are analysed. The problem of inaccessibility of mortgage lending for the general population is emphasized, which is mitigated both by market decisions of banks to reduce real mortgage rates and government initiatives to introduce and improve programs for affordable loans and housing. The practice of state programs in the housing market is analysed and the preservation of problems of their effective implementation is noted, including limited and instability of financing, the ambiguity of participation conditions, narrow target orientation, the inconsistency of responsibility of program participants. The peculiarities of the current mortgage lending are determined, among which the increase of new mortgage loans, the dominance of agreements on the secondary market, the limited number of mortgage lending banks, the provision of mortgage loans for a short period. New government initiatives to stimulate mortgage lending are considered, among the positive aspects of which is the priority of reducing the % of loan servicing, harmonization of relevant regulations, clarification of the procedure for participation. It is proposed to apply a systematic approach to the development of state support programs, which will be based on priorities by stimulating the growth of incomes and solvency of broad sections of citizens and the involvement of innovative developers in programs.
Keywords: state support; mortgage lending; housing stock; the housing market; deferred demand; stable development; the state program